Transferências financeiras em grupos de negócios: evidências em meio a crise econômica brasileira de 2020 - Stoever, Erick Pires (2022)
The formation of business groups occurs from the diversification of operations and the expansion of the complexity of the chain of command. The literature assesses that this formation benefits from the diversification and the scale gain that the structure provides. However, the majority partners can act for their own benefit to obtain greater gains, transferring resources between companies of the same group. This research evaluates, through a quasi-experiment, using the Difference-inDifferences (DID) method, the possibility that these intra-group transfers of resources are more common in times of economic crisis, such as the one generated in 2020 by the spread of coronavirus. This crisis was used as a framework for an exogenous shock. Thus, it was possible to verify the effect of the investment before and after the crisis, measuring its impact. The results revealed changes in the investment structures of companies belonging to groups. Group controllers transfer resources from companies with fewer investment opportunities to companies with greater opportunities. The results found also indicate that companies belonging to groups have a better internal and market performance during the crisis compared to companies that do not have this type of affiliation. This result allows the minority investor to have better arguments to invest in companies belonging to groups in times of economic crisis.